Contribution of green fertilization to the chemical, physical and biological characteristics of the soil and its influence on the nutrition of vegetables (Research, Society and Development, 2021)
Green manure is an ancient technique where the cultivation of plants specially designed to improve the physical, chemical and/or biological parameters of the soil is carried out. Such plants must have relevant characteristics such as high biomass production, ease of cultivation, rusticity, in addition to the biological nitrogen fixation capacity associated with plants of the Fabaceae family, which is widely explored. Therefore, the present literature review aimed to collect and gather information related to green manure and its effects on soil characteristics, influencing the nutrition of vegetables. Some of the most pronounced advantages of the technique are the maintenance of covered soil, which minimizes losses due to erosion, and the availability of nutrients that can be absorbed by economic crops. In addition, it was possible to identify that most studies date from the past decade, with few being published in recent years. The perceived tendency is for growth and space gain, due to the consolidation of benefits and change in the point of view of both farmers and consumers, who yearn for the consumption of food produced in a sustainable way.